2015
DOI: 10.4137/bmi.s35005
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Local and Systemic Cytokines in Bacterial Meningitis and its Relation with Severity and Long-Term Sequelae

Abstract: Bacterial meningitis (BM) is a pyogenic infection present in the subarachnoid space, potentially fatal and frequently associated with neurological sequelae. During BM, cytokines (CTs) are locally produced. We sought to determine the CTs’ clinical role as disease severity predictors in adults, which is not completely clear. Using a bead-based flow cytometric assay, levels of six CTs were determined in cerebrospinal fluid (CSF) and plasma from 18 adult BM patients and 19 uninfected controls. Long-term neurologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 57 publications
2
16
0
Order By: Relevance
“…These results were more recently supported when it was found that in patients with non-meningitis related sepsis, not only were cytokine levels higher in the CSF than in plasma, but also levels of CSF IL-6, IL-8, IL-10, IL-1β, and TNF-a, and plasma IL-10 and IL-12p70 were significantly higher in patients with severe sepsis than in those with sepsis [36].…”
Section: Clinical Effects Of Inflammatory Cytokinesmentioning
confidence: 78%
See 1 more Smart Citation
“…These results were more recently supported when it was found that in patients with non-meningitis related sepsis, not only were cytokine levels higher in the CSF than in plasma, but also levels of CSF IL-6, IL-8, IL-10, IL-1β, and TNF-a, and plasma IL-10 and IL-12p70 were significantly higher in patients with severe sepsis than in those with sepsis [36].…”
Section: Clinical Effects Of Inflammatory Cytokinesmentioning
confidence: 78%
“…Jason L. Siegel, Acute bacterial meningitis and stroke Additionally, higher CSF levels of IL-6 and IL-12p70 were correlated with worse long-term outcomes [36].…”
Section: Clinical Effects Of Inflammatory Cytokinesmentioning
confidence: 99%
“…This increase was not noted in the plasma from the same patient. We have described that after bacterial infection of the human meninges, a massive proinflammatory cytokine response occurs selectively in the CSF but not blood, and the magnitude of this response is correlated with the clinical severity and development of sequelae (Perdomo-Celis et al, 2015). Other neurotropic viruses such as herpes viruses are also known to induce the selective expression of IL-6 and IFN-g intrathecally after infection (Aurelius et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Immune-regulatory mechanisms in meningitis have been extensively investigated in small animal models 3, 4 and through correlative studies of body fluids in patients demonstrating a pleiotropic cytokine response. [5][6][7][8][9] To date, no individual cytokine or other endogenous immune regulator has been found to be sufficient for inducing fatal meningitis.…”
Section: Introductionmentioning
confidence: 99%
“…A prominent new agent under development as an investigational new drug (IND) is interleukin-10 (IL-10), a cytokine most often classified as anti-inflammatory, which can be detected in the nervous system of patients with meningitis 7,8 and (used as a therapeutic) is a candidate for treating a variety of CNS disorders such as multiple sclerosis and neuropathic pain. 10 In the case of analgesic testing of IL-10, gene vectors are used to deliver the cytokine to the intrathecal (i.t.)…”
Section: Introductionmentioning
confidence: 99%